Impact of Oral Commensal Bacteria on Degradation of Periodontal Connective Tissue in Mice. Issue 7 (1st July 2015) - Irie, Koichiro; Tomofuji, Takaaki; Ekuni, Daisuke; Morita, Manabu; Shimazaki, Yoshihiro; Darveau, Richard P.
Abstract : Background: Innate and adaptive immunosurveillance mechanisms in response to the normal commensal bacteria can affect periodontal innate defense status. However, it is still unclear how commensal bacteria contribute to the inflammatory responses of junctional epithelium (JE) and periodontal connective tissue (PCT). The aim of the present study is to investigate the contribution of commensal bacteria on inflammatory responses in JE and PCT in mice. Methods: The periodontal tissue of germ‐free (GF) and specific‐pathogen‐free (SPF) mice were compared at age 11 to 12 weeks (n = 6 per group). In this study, the number of neutrophils and expression of intercellular adhesion molecule (ICAM)‐1, fibroblast growth factor receptor (FGFR)‐1, matrix metalloproteinase (MMP)‐1, and MMP‐8 within the JE and the PCT are evaluated. The collagen density was also determined in PCT stained with picrosirius red (PSR). PSR staining combined with or without polarized light microscopy has been used to assess the organization and maturation of collagen matrix. Results: In the present findings, the area of JE in SPF mice was significantly greater than that in GF mice ( P <0.05). In addition, the JE and PCT in SPF mice showed greater migration of neutrophils and higher expression of ICAM‐1, FGFR‐1, MMP‐1, and MMP‐8 than those in GF mice ( P <0.05). Furthermore, the density of collagen in PCT in SPF mice was lower compared to GF mice ( P <0.05). Conclusion: These results indicate that commensal bacteria induced a low‐grade inflammatory state in JE and that such conditions may contribute to degradation of collagen in PCT in mice.